2014
DOI: 10.1111/vde.12112
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of anti‐Müllerian hormone in a dog with a Sertoli cell tumour

Abstract: Canine serum AMH concentrations, as measured by a human AMH enzyme-linked immunosorbent assay, may be useful as a marker for canine SCT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
19
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 10 publications
5
19
0
1
Order By: Relevance
“…Regarding another effect of hyperestrogenemia, the preputial cytology of Case 2 exhibited exfoliative, superficial epithelial cells similar to the vaginal cytology of female dogs in estrus, which corresponds with a report that the preputial cytology of male dogs that have hyperestrogenemia (>40 pmol/L) exhibited superficial epithelial cells [10]. Recently, it has been reported that neoplastic Sertoli cells in dogs produce a significantly high MIF level compared with healthy Sertoli cells [11, 12]. If we had detected the level of AMH in both cases, the patient in Case 2, which had SCT, might have exhibited a higher level of AMH compared with the patient in Case 1 with no SCT.…”
Section: Discussionsupporting
confidence: 81%
“…Regarding another effect of hyperestrogenemia, the preputial cytology of Case 2 exhibited exfoliative, superficial epithelial cells similar to the vaginal cytology of female dogs in estrus, which corresponds with a report that the preputial cytology of male dogs that have hyperestrogenemia (>40 pmol/L) exhibited superficial epithelial cells [10]. Recently, it has been reported that neoplastic Sertoli cells in dogs produce a significantly high MIF level compared with healthy Sertoli cells [11, 12]. If we had detected the level of AMH in both cases, the patient in Case 2, which had SCT, might have exhibited a higher level of AMH compared with the patient in Case 1 with no SCT.…”
Section: Discussionsupporting
confidence: 81%
“…A higher concentration of AMH in intact dogs than in castrated dogs has been reported previously (Ano and others 2014). Likewise, evaluating AMH concentrations in castrated, intact and cryptorchid stallions, Claes and others (2013) found significantly higher concentrations of AMH in intact and ­cryptorchid stallions than in castrated stallions.…”
supporting
confidence: 61%
“…Ano and others (2014) observed a considerably higher concentration of AMH in a cryptorchid dog with Sertoli cell tumour than in intact dogs. Claes and others (2013) reported higher concentrations of AMH in cryptorchid stallions than in intact stallions.…”
mentioning
confidence: 67%
“…In males, AMH is produced by the Sertoli cell [5]. Anti-Müllerian hormone assays have also been used to evaluate fertility and gonadal pathology in humans and domestic animals [6][7][8][9][10]. In women, serum AMH concentrations decrease with age, independently of the menstrual cycle and the number of pregnancies [7].…”
Section: Introductionmentioning
confidence: 99%